The Evolving Landscape Of Multimodal Transportation: Preparing Indonesian Cadets For The Future - Fahmi Umasangadji; Marihot Simanjuntak; April Gunawan Malau; Larsen Barasa; Marudut Bernadtua Simanjuntak (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research explores the preparedness of Indonesian cadets in multimodal transportation, focusing on 50 cadets from a transportation institution in Jakarta. Qualitative methods, including interviews and focus groups, were used to assess their knowledge, skills, and adaptability to emerging trends and technologies. The findings indicate that while cadets demonstrate a strong understanding of key concepts and principles, there are areas for improvement, particularly in problem-solving skills and adaptability to new technologies. Recommendations include enhancing problem-solving skills, incorporating training on emerging technologies, fostering collaboration and interdisciplinary learning, providing continuous professional development opportunities, strengthening industry-academia collaboration, evaluating and updating curriculum regularly, and promoting lifelong learning and professionalism. These recommendations aim to enhance the preparedness of Indonesian cadets and ensure that educational programs align with the evolving needs of the transportation industry.